Regioselective C2 Oxidative Olefination of Indoles and Pyrroles through Cationic Rhodium(III)‐Catalyzed CH Bond Activation. Issue 36 (23rd July 2013) - Li, Bin; Ma, Jianfeng; Xie, Weijia; Song, Haibin; Xu, Shansheng; Wang, Baiquan
<x xml:space="preserve">Abstract</x> Be economic with your atoms! An efficient Rh‐catalyzed oxidative olefination of indoles and pyrroles with broad substrate scope and tolerance is reported (see scheme). The catalytic reaction proceeds with excellent regio‐ and stereoselectivity. The directing group N, N‐dimethylcarbamoyl was crucial for the reaction and could be removed easily.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>